A study on anti-ulcer potential of the ethanol extract of stem bark of F. religiosa against in vivo indomethacin (International Journal of Medicine and Medical Sciences, 2019)
Ficus religiosa is being used in Ayurvedic and Malay traditional medicine for the treatment of various diseases including gastric ulcer. Considering the above claims, the present work was undertaken to validate the anti-ulcer potential of the ethanol extract of stem bark of F. religiosa against in vivo indomethacin- and cold restrained stress-induced gastric ulcer, and pylorus ligation assays. The extract (100, 200 and 400 mg/kg) significantly (P